Can serial cerebral MRIs predict the neuronopathic phenotype of MPS II?. Issue 3 (25th January 2021) - Vollebregt, Audrey A. M.; Ebbink, Berendine J.; Rizopoulos, Dimitris; Lequin, Maarten H.; Aarsen, Femke K.; Shapiro, Elsa G.; van der Ploeg, Ans T.; van den Hout, Johanna M. P.
Abstract: Objective: To advance the prediction of the neurocognitive development in MPS II patients by jointly analyzing MRI and neurocognitive data in mucopolysaccharidosis (MPS) II patients. Methods: Cognitive ability scores (CAS) were obtained by neuropsychological testing. Cerebral MRIs were quantified using a disease‐specific protocol. MRI sumscores were calculated for atrophy, white‐matter abnormalities (WMA) and Virchow‐Robin spaces (VRS). To distinguish between atrophy and hydrocephalus the Evans' index and the callosal angle (CA) were measured. A random effects repeated measurement model was used to correlate CAS with the three MRI sumscores. Results: MRI (n = 47) and CAS scores (n = 78) of 19 male patients were analyzed. Ten patients were classified as neuronopathic and nine as non‐neuronopathic. Neuronopathic patients had normal cognitive development until age 3 years. Mental age plateaued between ages 3 and 6, and subsequently declined with loss of skills at a maximum developmental age of 4 years. MRIs of neuronopathic patients showed abnormal atrophy sumscores before CAS dropped below the threshold for intellectual disability (<70). White‐matter abnormalities (WMA) and brain atrophy progressed. The calculated sumscores were inversely correlated with CAS ( r  = −.90 for atrophy and −.69 for WMA). This was not biased by the influence of hydrocephalus as shown by measurement of the Evans' and callosal angle. Changes over time in the Virchow‐Robin spaces (VRS) on MRI were minimal. Conclusion: In our cohort, brain atrophy showed a stronger correlation to a decline in CAS when compared to WMA. Atrophy‐scores were higher in young neuronopathic patients than in non‐neuronopathic patients and atrophy was an important early sign for the development of the neuronopathic phenotype, especially when observed jointly with white‐matter abnormalities.